Edukasi Pencegahan HIV-AIDS dan Mother to Child Transmission of HIV Pada Wanita Usia Subur Dalam Mendukung Indonesia Bebas AIDS 2030 - Tri Novianty Mansyur; Yumi Abimulyani; Neny San Agustina Siregar; Yuliana Yacinta Kainde (LPPM Akbid Harapan Ibu Pekalongan, 2023)
Acquired Immunodeficiency Syndrome (AIDS) is a type of infection caused by the Human Immunodeficiency Virus (HIV) which attacks the immune system and causes susceptibility to a disease. HIV/AIDS cases are like an iceberg phenomenon because fewer people are checking their health status than actually happened. There are still high rates of HIV/AIDS and Mother to Child Transmission (MTCT) of HIV in the world and in Indonesia and even in Papua.So it is necessary to educate various lines of society. The purpose of this community service is to increase the knowledge of women of childbearing age about HIV/AIDS prevention and MTCT of HIV. The educational methods used were (1) Pre-test (2) Dissemination of material and leaflet (3) Evaluation of the results of educational activities with a post-test. The result of this community service was an increase in knowledge about HIV/AIDS and accompanied by MTCT of HIV. This proves that there is a positive increase after the educational intervention given.